Zoomingin on quartzitic outcrops: micro-habitat influences on flora and vegetation - Badia, Clara da Cruz Vidart; Messias, Maria Cristina Teixeira Braga; Echternacht, Livia (Rodriguésia, 2021)
Abstract Rock outcrop vegetation is recognized worldwide by its singular and biodiverse flora. Campo Rupestre forms hyperdiverse mosaics in rocky environments across a wide latitudinal and altitudinal gradient, with high species turnover at macro- and micro-scales. The surrounding biomes, climate, and geological formations are the main drivers of species turnover on a macro-scale while micro-habitat seems to be the main one determining the peculiarities of the Campo Rupestre on a micro-scale. In a quartzitic Campo Rupestre area we evaluate how the outcrop micro-habitats influence floristic composition and functional traits. The study area is located in the municipality of Ouro Preto, Minas Gerais state, southeastern Brazil. Two main outcrop habitats were considered: top surfaces, with bare rock, shallow depressions and ephemeral ponds; and lateral surfaces, with clefts and crevices. We recorded the vascular species, their respective life-forms (according to Raunkiaer’s system) as well as their coverage in 18 plots. We identified 71 species in 31 families. The floristic spectra and species composition were similar between top and lateral surfaces. There was no significant difference among the vegetational spectra. However, hemicryptophytes were slightly dominant on top, while on the sides chamaephytes were the dominant life-form. Understanding plant adaptations to these environments provides insights into the mechanisms underlying geomorphological heterogeneity in plant communities. Resumo A vegetação de afloramentos rochosos é reconhecida mundialmente pela biodiversidade e singularidade de sua flora. O Campo Rupestre forma mosaicos hiperdiversos em ambientes rochosos distribuídos ao longo de um amplo gradiente latitudinal e altitudinal, com altas taxas de substituição de espécies em macro e microescalas. Em macroescala, os biomas adjacentes, clima e formações geológicas influenciam as taxas de substituição de espécies, enquanto os micro-habitats parecem influenciar as peculiaridades do Campo Rupestre em microescala. Este estudo foi realizado no município de Ouro Preto, Minas Gerais, Brasil. Visamos avaliar como os micro-habitats de afloramentos rochosos quartzíticos determinam a composição florística e os atributos funcionais considerando dois habitats principais: superfície superior, com rocha exposta, depressões rasas e poças efêmeras; e superfície lateral, com fendas e fissuras. Espécies vasculares e suas respectivas formas de vida e cobertura foram registradas em 18 parcelas. Identificamos 71 espécies pertencentes a 31 famílias. O espectro florístico e a composição de espécies foram similares entre os habitats. Não houve diferença significativa entre os espectros vegetacionais. Entretanto, hemicriptófitas foram ligeiramente dominantes na superfície superior e caméfitas, na lateral. Compreender as adaptações das plantas a esses ambientes fornece informações sobre os mecanismos subjacentes à heterogeneidade geomorfológica nas comunidades vegetais.